2013
DOI: 10.1080/17461391.2013.819382
|View full text |Cite
|
Sign up to set email alerts
|

A notational analysis of shot characteristics in top‐level table tennis players

Abstract: This study aimed to analyse selected shot characteristics in top-level table tennis matches, with a special focus on comparing the playing style of Asian and European players. Ten men's matches played by 20 top-ranked players (14 Asians and 6 Europeans) were analysed. The indicators examined were the area of ball bouncing for serves (n =918), and the stroke type, footwork type and shot outcome for other shots (n=3692). The interrelationships between variables were analysed using chi-squared tests, log-linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 13 publications
4
101
3
3
Order By: Relevance
“…Considering that the input data in this study is relatively simple, with only the rally lengths, server and winner known, it is possible to draw conclusions about the general structure of a table tennis game. Some interesting questions that are relevant in table tennis practice, like the impact of transitions between stroke techniques or stroke positions, as examined in other studies (Zhang, 2006;Pfeiffer et al, 2010;Malagoli-Lanzoni et al, 2014), can not be answered with the available data. However, since the simulation method itself is independent from the information contained in the input data, it would be possible to examine these features if it were included in the dataset.…”
Section: Discussionmentioning
confidence: 77%
“…Considering that the input data in this study is relatively simple, with only the rally lengths, server and winner known, it is possible to draw conclusions about the general structure of a table tennis game. Some interesting questions that are relevant in table tennis practice, like the impact of transitions between stroke techniques or stroke positions, as examined in other studies (Zhang, 2006;Pfeiffer et al, 2010;Malagoli-Lanzoni et al, 2014), can not be answered with the available data. However, since the simulation method itself is independent from the information contained in the input data, it would be possible to examine these features if it were included in the dataset.…”
Section: Discussionmentioning
confidence: 77%
“…Previous research (Malagoli Lanzoni et al, 2014) has shown that the server's advantage (i.e. the probability of winning a rally) is higher in relatively short rallies up to the third shot, while the probability of winning a rally for the receiver increases after the fourth-sixth shot.…”
Section: Introductionmentioning
confidence: 87%
“…CONTACT miguel-Ángel Gómez magor_2@yahoo.es information in a descriptive and comparative way (Loh & Krasilshchikov, 2015;Malagoli Lanzoni, Di Michele, & Merni, 2014;Zhang, Liu, Hu, & Liu, 2013), or in a probabilistic way (Pfeiffer, Zhang, & Hohmann, 2010). This research has focused on technical-tactical evaluations (Malagoli Lanzoni et al, 2014;Pfeiffer et al, 2010;Zhang et al, 2013) and the structural demands of the game (Leite, Barbieri, Miyagi, Malta, & Zagatto, 2017;Loh & Krasilshchikov, 2015). To the best of our knowledge, no predictive studies have been conducted to investigate into the influence of contextual factors on serve and reception effectiveness during table tennis matches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, jumping exercises are advocated as a suitable approach for demanding sports explosiveness and develop vertical jump including table tennis (Zagatto et al, 2008;Malagoli Lanzoni et al, 2014;Munivrana et al, 2015).…”
Section: The Performance Of the Vertical Jumpmentioning
confidence: 99%